Overview of infectious complications among CAR T- cell therapy recipients - Arya, Swarn; Shahid, Zainab (Frontiers in Oncology, 2024)
Chimeric antigen receptor-modified T cell (CAR-T cell) therapy has revolutionized the management of hematological malignancies. In addition to impressive malignancy-related outcomes, CAR-T cell therapy has significant toxicity-related adverse events, including cytokine release syndrome (CRS), immune effector cell associated neurotoxicity syndrome (ICANS), immune effector cell-associated hematotoxicity (ICAHT), and opportunistic infections. Different CAR-T cell targets have different epidemiology and risk factors for infection, and these targets result in different long-term immunodeficiency states due to their distinct on-target and off-tumor effects. These effects are exacerbated by the use of multimodal immunosuppression in the management of CRS and ICANS. The most effective course of action for managing infectious complications involves determining screening, prophylactic, and monitoring strategies and understanding the role of immunoglobulin replacement and re-vaccination strategies. This involves considering the nature of prior immunomodulating therapies, underlying malignancy, the CAR-T cell target, and the development and management of related adverse events. In conclusion, we now have an increasing understanding of infection management for CAR-T cell recipients. As additional effector cells and CAR-T cell targets become available, infection management strategies will continue to evolve.